2016
DOI: 10.1074/jbc.m116.718031
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Caenorhabditis elegans Degenerin Channel by Shear Stress Requires the MEC-10 Subunit

Abstract: Mechanotransduction in Caenorhabditis elegans touch receptor neurons is mediated by an ion channel formed by MEC-4, MEC-10, and accessory proteins. To define the role of these subunits in the channel's response to mechanical force, we expressed degenerin channels comprising MEC-4 and MEC-10 in Xenopus oocytes and examined their response to laminar shear stress (LSS). Shear stress evoked a rapid increase in whole cell currents in oocytes expressing degenerin channels as well as channels with a MEC-4 degenerin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 52 publications
0
22
1
Order By: Relevance
“…These findings suggest that these two proteins are required for the isolation-induced morphological modification of the PVD and represent an example in which the response to harsh touch is independent of the structural alteration of the PVD. Since MEC-10 is important for laminar shear stress 41 and touch 21 we suggest that this channel and its possible partners from the DEG/ENaC family, such as DEGT-1, ASIC-1 and DEL-1 25, 43, 44 , affect the structure and the function of the PVD independently, in an experience-dependent manner and contrary to the original hypothesis by Hall and Treinin 39 .…”
Section: Main Textcontrasting
confidence: 61%
See 1 more Smart Citation
“…These findings suggest that these two proteins are required for the isolation-induced morphological modification of the PVD and represent an example in which the response to harsh touch is independent of the structural alteration of the PVD. Since MEC-10 is important for laminar shear stress 41 and touch 21 we suggest that this channel and its possible partners from the DEG/ENaC family, such as DEGT-1, ASIC-1 and DEL-1 25, 43, 44 , affect the structure and the function of the PVD independently, in an experience-dependent manner and contrary to the original hypothesis by Hall and Treinin 39 .…”
Section: Main Textcontrasting
confidence: 61%
“…Thus, the structure of the PVD is sensitive to activity and cation influx via DEG/ENaCs. To determine whether the morphological effect on PVD structure is also mediated by mechanical (like friction 41 and collisions 21 ), rather than chemical cues, we used glass beads under isolated conditions, to test the effect on the morphology. We found that mechano-stimulation induced by glass beads did not restore the fraction of ectopic branching, but it did significantly increase the number of straight quaternary branches and decreased the percentage of self-avoidance defects (compared with isolated animals without beads, Fig.…”
Section: Main Textmentioning
confidence: 99%
“…In contrast to other cell lines, oocytes have a native and differentiated ECM that is not challenged by passaging during cultivation. They are also an established model for investigating the effects of SF on ENaC (Carattino et al, 2004;Althaus et al, 2007), K + channels (Hoger et al, 2002), and MEC channels (Shi et al, 2016).…”
Section: Sf-dependent Activation Of Enac Involves the Extracellular Mmentioning
confidence: 99%
“…Recently, we employed this technique to examine the regulation of MEC-4 and MEC-10 by LSS. These channel forming subunits are members of the ENaC/degenerin family expressed in C. elegans that are required for gentle touch in worms (Driscoll and Chalfie, 1991; Shi et al , 2016). Other investigators have employed the technique describe here to study the response of K + channels expressed in the vasculature to LSS (Hoger et al , 2002; Fronius et al , 2010).…”
Section: [Background]mentioning
confidence: 99%
“…Epithelial and endothelial cells are exposed to laminar shear stress (LSS), a tangential force exerted by flowing fluids against the wall of vessels and epithelia. The protocol outlined herein has been used to examine the response of ion channels expressed in Xenopus oocytes to LSS (Hoger et al , 2002; Carattino et al , 2004; Shi et al , 2006). The Xenopus oocyte is a reliable system that allows for the expression and chemical modification of ion channels and regulatory proteins (George et al , 1989; Palmer et al , 1990; Sheng et al , 2001; Carattino et al , 2003).…”
mentioning
confidence: 99%